Role of Students in Accreditation - Babiker, Adil A (Gezira Journal of Health Sciences; Vol 14 No 2 (2018), 2018)
Accreditation in medical education is important for the medical schools to improve the quality of education, for health services and community to improve the quality of health services and for students good chances for employment and postgraduate studies locally and abroad, students had a major role in accreditation.